UNEMPLOYMENT IN SHAPING RURAL-URBAN MIGRATION PATTERNS IN POLAND - Nina Drejerska; Kamila Wojciechowska-Łapszo (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of the research was to determine the relationship between regional unemployment and internal migration in Poland, with a focus on non-agglomeration, low-density areas. Drawing on average data from 2020 to 2023, the analysis investigates how the proportion of registered unemployed individuals among the working-age population relates to internal migration balances across voivodeships. The results indicate a clear inverse association: regions with higher unemployment tend to experience greater net outflows of population. This pattern is consistent with economic migration theory, which suggests that individuals relocate in response to regional disparities in employment opportunities. The analysis highlights notable contrasts between regions with persistently high unemployment and negative migration balances, and those with stronger labour markets and positive migration trends. These findings underscore the importance of integrating migration policy with labour market planning, particularly in rural areas facing demographic decline. The study also points to the need for further research into the temporal dynamics of migration, including potential lag effects between economic conditions and population movements.